2020
DOI: 10.1021/acsami.0c03257
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Laser-Annealed IZO Flexible Device as a Sensitive H2S Sensor at Room Temperature

Abstract: A metal-oxide material (indium zinc oxide [IZO]) device with near-infrared (NIR) laser annealing was demonstrated on both glass and bendable plastic substrates (polycarbonate, polyethylene, and polyethylene terephthalate). After only 60 s, the sheet resistance of IZO films annealed with a laser was comparable to that of thermal-annealed devices at temperatures in the range of 200°C-300°C (1 hr). XPS, ATR, and AFM were used to investigate the changes in the sheet resistance and correlate them to the composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In Figure 3a, the changes observed under thermal annealing are consistent with those reported previously. [ 21 ] A significant decrease in vacancies was observed with an increase in the M‐O, which corresponds to the condensation reactions induced by thermal treatments. The moderate temperature leads to amorphous materials, which explain the relatively high level of vacancies in the final material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 3a, the changes observed under thermal annealing are consistent with those reported previously. [ 21 ] A significant decrease in vacancies was observed with an increase in the M‐O, which corresponds to the condensation reactions induced by thermal treatments. The moderate temperature leads to amorphous materials, which explain the relatively high level of vacancies in the final material.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we recently showed that the use of NIR dyes can significantly improve the NIR laser curing of sol–gel indium‐zinc‐oxide (IZO) materials and allow their use as gas sensors. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall current increased with increasing humidity. This could be due to the adsorption of water on the ZnO surface and its subsequent dissociation into hydroxide and protons, which could lead to enhanced conductivity due to a proton hopping mechanism . The presence of water would also allow ammonia to adsorb onto the surface as ammonium hydroxide, which could enhance its reactivity and explain the faster response at higher humidity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9,10 ] These laser‐based approaches include the synthesis of conductive silver patterns on polyimide [ 11 ] and polyurethane, [ 12 ] crystallization of BiVO 4 films, [ 13 ] carbonization of organic particle films on PET, [ 14 ] and metallization of a Cu‐containing polymer, [ 15 ] and photothermal annealing of indium zinc oxide on different polymers. [ 16 ] The introduction of different materials in the bulk polymer was exploited to enable laser processing for polymer marking, including additives such as graphene/polystyrene, [ 17 ] antimony trioxide polystyrene, [ 18 ] TiO 2 nanoparticles, [ 19 ] and oxides like Fe 3 O 4 , ZrO 2 , [ 20 ] and SnO 2 . [ 21 ] For this application, the laser‐driven embedding of dyes into the surfaces of polymers is particularly interesting by combining spray coating with laser curing for marking purposes.…”
Section: Introductionmentioning
confidence: 99%